1. Simplify 49^3/2.
My answer: 343?
2. Simplify 5^�ãx^25y^125.
My answer: x^5y^25?
3. When the polynomial 5x - 2x + 8x^2 - 7 is written in standard form, what is the leading coefficient?
My answer: -2?
4. Classify the polynomial 5x^2 + 9x + 1 according to tis degree and number of terms.
My answer: Quadratic trinomial?
5. Genie has 100 feet of fence with which to make a rectangular cage for her rabbit. If she uses the wall of her house as one side, the area of the cage in square feet is given by the polynomial -2x^2 + 100w, where w is the width of the cage in feet. What is the area of the cage if the width is 15 feet?
My answer: 1,050 feet?
6. Add (5x^2 - 2x + 9) + (2x^2 - 4).
My answer: 7x^4 - 2x + 5?
7. Subtract (10a^2 - 6a) - (7a^2 - 8a).
My answer: 3a^2 - 14a?
8. Multiply (-5rs^4)(3r^5s^2).
My answer: -15r^6s^6?
9. (3x - 4)^2
My answer: 6x^2 - 24x + 8?
10. (2x + 4)(2x - 4)
My answer: 4x^2 - 8?
2 answers
The way you typed it --- 117649/2
2. can't read the question
3. the leading term in standard notation would be 8x^2
so leading coefficient is 8
4. correct
5. the x is undefined in your problem
6. 7x^2 - 2x + 5, the exponent is not affected when adding like terms
7. 3a^ + 2a
8. correct
9. 6x^2 - 24x + 16 , 4 x 4 = 16 not 8
10. 4x^2 - 16
looks like somebody has some serious studying to do.
If 49^3/2 mean 49 ( 3 / 2 ) then:
49 ( 3 / 2 ) = [ ( 49 ) ^ 3 ] ^ ( 1 / 2 ) =
[ ( 49 ) ^ ( 1 / 2) ] ^ 3 =
sqrt ( 49 ) ^ 3 =
7 ^ 3 = 343
Correct
2. What is 5^�ãx^25y^125 ?
3.
5 x - 2 x + 8 x ^ 2 - 7 =
8 x ^ 2 + 3 x - 7
In a polynomial, the coefficient of the term with the highest degree is called the leading coefficient.
So the leading coefficient = 8
4.
Correct
5.
x = the length of the side parallel to the building
w = the width of the cage
x + 2 w = 100
Subtract 2 w to both sides
x + 2 w - 2 w = 100 - 2 w
x = 100 - 2 w
Area = length * width
A = x * w =
( 100 - 2 w ) * w =
100 w - 2 w ^ 2 =
- 2 w ^ 2 + 100 w
NOT ( - 2 x ^ 2 + 100 w )
A = - 2 w ^ 2 + 100 w
= - 2 * 15 ^ 2 + 100 * 15 =
- 2 * 225 + 1500 =
-450 + 1500 =
1050 ft ^ 2
6.
( 5 x ^ 2 - 2 x + 9 ) + ( 2 x ^ 2 - 4 ) =
5 x ^ 2 - 2 x + 9 + 2 x ^ 2 - 4 =
5 x ^ 2 + 2 x ^ 2 - 2 x + 9 - 4 =
7 x ^ 2 - 2 x + 5
7.
( 10 a ^ 2 - 6 a ) - ( 7 a ^ 2 - 8 a ) =
10 a ^ 2 - 6 a - 7 a ^ 2 - ( - 8 a ) =
10 a ^ 2 - 6 a - 7 a ^ 2 + 8 a =
10 a ^ 2 - 7 a ^ 2 - 6 a + 8 a =
3 a ^ 2 + 2 a
8.
Correct
9.
( a - b ) ^ 2 = a ^ 2 - 2 * a * b + b ^ 2
( 3 x - 4 ) ^ 2 =
( 3 x ) ^ 2 - 2 * 3 x * 4 + 4 ^ 2 =
9 x ^ 2 - 6 x * 4 + 16 =
9 x ^ 2 - 24 x + 16
10.
( 2 x + 4 ) * ( 2 x - 4 ) =
2 x * 2 x + 2x * 4 - 4 * 2 x - 4 * 4 =
4 x ^ 2 + 8 x - 8 x - 16 =
4 x ^ 2 - 16
OR
( a + b ) * ( a - b ) = a ^ 2 - b ^ 2
( 2 x + 4 ) * ( 2 x - 4 ) =
( 2 x ) ^ 2 - 4 ^ 2 =
4 x ^ 2 - 16